PEMBERIAN HARTA ZAKAT KEPADA MASJID MENURUT WAHBAH ZUHAILI - Aria Sandra; Edwar Edwar (SYARIAH: Journal of Islamic Law, 2021)
This study was raised about Wahbah Zuhaili's opinion on the giving of zakat to mosques, in this case the author conducted a study of a legal view according to Wahbah Zuhaili who had different views with Yusuf Qardhawi. As for the formulation of the problem in this study, namely how is Wahbah Zuhaili's opinion about giving zakat assets to mosques and how is Wahbah Zuhaili's Ijtihad method about giving zakat assets to mosques. Based on the data collection method, this research is a library research, namely using library materials as a source of data in the form of Wahbah Zuhaili's works related to the topic of these problems. The findings of this study are that Wahbah Zuhaili's opinion that giving zakat to mosques is not allowed because the people who are entitled to receive zakat are those who have ownership (on behalf of individuals), and he limits only those eight groups who are entitled to receive zakat and hinders others. to be able to get it because at the beginning of the verse there is the word innama, and he also uses his ijtihad regarding not being allowed to give zakat to mosques, namely by using the verses of the Qur'an, Surah Al-Taubah: 60, and QS. Al-Shaff: 4, and also the consensus of the scholars. From the explanation above, it can be concluded that giving zakat to mosques is not allowed because it is general in nature and also mosques are not mentioned as snaf zakat in the Qur'an.